Do Resource-Rich Provinces Perform Lower Democratization Progress? Estimating Oil Impact on Democracy Indicators in Indonesia - Hilmawan, Rian (Jurnal Ekonomi & Studi Pembangunan, 2021)
This study examined whether oil dependence affected democracy quality by referring to provincial-level data in Indonesia. While physical quantity production was used to measure oil dependence, democracy was measured based on the Indonesian Democracy Index (IDI). Static panel data analysis was employed to control unobserved time-invariant characteristics of each province, including a robust Driscoll and Kraay (D-K) standard error model for the general forms of cross-sectional dependence when dealing with panel observation. The results showed that oil-dependent provinces tended not to have weak democratic qualities. The effects were also robust when democracy was separated into three main elements of the IDI: political rights, civil liberties, and democratic institutions, or when an alternative measure of dependency was used. Interestingly, this study found that oil dependence had a stronger effect on democracy in provinces with a lack of oil than in Sumatra and Kalimantan, globally known as dominant resource locations.